Multi-sector Economic Models with Continuous Adaptive Expectations - Burmeister, Edwin; Graham, Daniel A. (Review of Economic Studies, 1974)
Journal Article Multi-sector Economic Models with Continuous Adaptive Expectations Get access Edwin Burmeister, Edwin Burmeister University of Pennsylvania Search for other works by this author on: Oxford Academic Google Scholar Daniel A. Graham Daniel A. Graham Duke University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 41, Issue 3, July 1974, Pages 323–336, https://doi.org/10.2307/2296752 Published: 01 July 1974